Protective role of mitochondrial superoxide dismutase against high osmolarity, heat and metalloid stress in saccharomyces cerevisiae - Dziadkowiec, D; Krasowska, A; Liebner, A; Sigler, K (Folia microbiologica, 2007)
Superoxide dismutases, both cytosolic Cu, Zn-SOD encoded by SOD1 and mitochondrial Mn-SOD encoded by SOD2, serve Saccharomyces cerevisiae cells for defense against the superoxide radical but the phenotypes of sod1A and sod2delta mutant strains are different. Compared with the parent strain and the sod1delta mutant, the sod2delta mutant shows a much more severe growth defect at elevated salt concentrations, which is partially rescued by 2 mmol/L glutathione. The growth of all three strains is reduced at 37 degrees C, the sod2delta showing the highest sensitivity, especially when cultured in air. Addition of 1 mmol/L glutathione to the medium restores aerobic growth of the sod1delta mutant but has only a minor effect on the growth of the sod2delta strain at 37 degrees C. The sod2delta strain is also sensitive to AsIIl and AsV and its sensitivity is much more pronounced under aerobic conditions. These results suggest that, unlike the Sodlp protein, whose major role is oxidative stress defense, Sod2p also plays a role in protecting S. cerevisiae cells against other stresses--high osmolarity, heat and metalloid stress.
Keywords: kultivační média; Glutathione; Superoxide Dismutase; vysoká teplota; osmolární koncentrace; aerobióza; Osmolar Concentration; Saccharomyces cerevisiae Proteins; Sodium Chloride; superoxiddismutasa 1; mitochondrie; Culture Media; superoxiddismutasa; Mitochondria; Hot Temperature; chlorid sodný; glutathion; arsen; Superoxide Dismutase-1; Saccharomyces cerevisiae; Aerobiosis; Saccharomyces cerevisiae - proteiny; Arsenic